2014
DOI: 10.1039/c4cp00775a
|View full text |Cite
|
Sign up to set email alerts
|

Ozonolysis of methyl oleate monolayers at the air–water interface: oxidation kinetics, reaction products and atmospheric implications

Abstract: Ozonolysis of methyl oleate monolayers at the air-water interface results in surprisingly rapid loss of material through cleavage of the C=C bond and evaporation/dissolution of reaction products. We determine using neutron reflectometry a rate coefficient of (5.7 ± 0.9) × 10(-10) cm(2) molecule(-1) s(-1) and an uptake coefficient of ∼3 × 10(-5) for the oxidation of a methyl ester monolayer: the atmospheric lifetime is ∼10 min. We obtained direct experimental evidence that <2% of organic material remains at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 39 publications
(65 reference statements)
3
58
0
Order By: Relevance
“…Therefore, the retention of the organic character at the air-water interface differs fundamentally between the different surfactant species: the fatty acids studied form products with a yield of ∼ 20 % that are stable at the air-water interface while the NO 3 -initiated oxidation of the methyl ester rapidly removes the organic character from the surface of the aqueous droplet. A similar difference (King et al, 2009;Pfrang et al, 2014;Sebastiani et al, 2015) between methyl ester and parent fatty acid has been found for the ozonolysis of d 34 OA and d 33 MO, but the retention of 20 % of organic material at the air-water interface is even more surprising for the more highly reactive nitrate radicals. The film-forming potential of the reaction products thus strongly depends on the head group properties.…”
Section: Head Groupsupporting
confidence: 63%
See 2 more Smart Citations
“…Therefore, the retention of the organic character at the air-water interface differs fundamentally between the different surfactant species: the fatty acids studied form products with a yield of ∼ 20 % that are stable at the air-water interface while the NO 3 -initiated oxidation of the methyl ester rapidly removes the organic character from the surface of the aqueous droplet. A similar difference (King et al, 2009;Pfrang et al, 2014;Sebastiani et al, 2015) between methyl ester and parent fatty acid has been found for the ozonolysis of d 34 OA and d 33 MO, but the retention of 20 % of organic material at the air-water interface is even more surprising for the more highly reactive nitrate radicals. The film-forming potential of the reaction products thus strongly depends on the head group properties.…”
Section: Head Groupsupporting
confidence: 63%
“…Nitrate radicals, NO 3 , were produced in situ from the reaction of O 3 with NO 2 . O 3 was generated by the exposure of molecular oxygen to UV light (the procedure has been described elsewhere; Pfrang et al, 2014). [NO 3 ] was regulated by changing the flow rate of NO 2 in the range 0.045-0.23 dm 3 min −1 while [O 3 ] was kept constant at 3.9 ppm (i.e.…”
Section: Gas Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Led by Christian Pfrang from Reading University, UK, the team studied the oxidation, by ozone, of organic monolayers at the air-liquid interface as a proxy for what is happening on the surface of aerosol droplets in clouds. 3 The interest arises from the fact that the lifetime of the droplets, which influences how much heat from sunlight gets to the lower atmosphere, is affected by their coating with organic material. The team showed that the surface reactions were much faster than could have been predicted before as methyl oleate has an atmospheric lifetime of just a few minutes.…”
Section: Neutron Reflectometrymentioning
confidence: 99%
“…We found that flash photolysis at 193 nm has not been attempted before for the generation of NO 3 , despite what is stated in Table II.19 in : the experiments referred to were only performed at 248 nm rather than 193 nm . We thus conducted the experiments presented here to establish if this method is a suitable source for NO 3 and can be applied for future experimental studies at the air–water interface (compare for an example of such experiments at the air–water interface).…”
Section: Introductionmentioning
confidence: 99%